Systemic venous anomalies in the Middle East - Corno, Antonio F.; Alahdal, Sami A.; Das, Karuna M. (Frontiers in Pediatrics, 2013)
Introduction: Systemic venous anomalies are quite rare and can be associated with congenital heart disease requiring surgery. Materials and Methods: All consecutive patients (pts) undergoing surgery for congenital heart defects were retrospectively analyzed for presence of systemic venous anomalies: (a) Persistent left superior vena cava (PLSVC) (b) Inferior vena cava (IVC) interruption (c) Retro-aortic innominate vein Results: From 9/2010 to 5/2012 155 pts, median age 7 months, mean age 1.3 years (3 days–50 years), median weight 4 kg, mean weight 7.2 kg (0.6–110 kg) underwent congenital heart surgery. Twenty-nine systemic venous anomalies were identified in 28/155 patients (=18.1%). PLSVC was present in 21 pts (=13.5%), median age 4 months, mean age 2.7 years (3 days–22 years), median weight 6 kg, mean weight 10.1 kg (2.4–43.0 kg). IVC interruption was identified in 5 pts (=3.2%), median age 2 months, mean age 5.4 years (30 days–26 years), median weight 3.7 kg, median weight 17 kg (2.3–68.0 kg). Retro-aortic innominate vein was diagnosed in 3 pts (=1.9%), median age 5 years, mean age 3.7 years (10 months–5 years), median weight 12 kg, mean weight 10.1 kg (4.5–14 kg). Complete pre-operative diagnosis was obtained in 14/28 (=50%) pts with echocardiography and in other 8/28 (=28.6%) only after computed tomography (CT) scan, for a total of 22/28 (=78.6%) correct pre-operative diagnosis. In 6/28 (=21.4%) patients the diagnosis was intra-operative. Total incidence of systemic venous anomalies was 18.1% (vs. 4% in the literature, P = 0.0009), with presence of PLSVC = 13.5% (vs. 0.3–4.0%, respectively P = 0.0004 and P = 0.0012), IVC interruption = 3.2% (vs. 0.1–1.3%, N.S.), and retro-aortic innominate vein = 1.9% (vs. 0.2–1%, N.S.). Conclusions: Our study showed an incidence of systemic venous anomalies in Middle Eastern pts with congenital heart defects higher than previously reported. In 78.6% of pts the diagnosis was correctly made before surgery (echocardiography or CT scan), with 21.4% of complete diagnosis made at surgery. A careful pre-operative screening should be performed in all pts with congenital heart defects from this region to better identify all systemic venous anomalies for a more accurate surgical planning.